A STUDY OF IONOSPHERIC REFRACTION OF RADIO WAVES FROM OBSERVATIONS OF COSMIC RADIO SOURCES USING THE RADIO TELESCOPE URAN-4 - Galanin, V. V.; Derevyagin, Ya. V.; Derevyagin, V. G. (Одеські астрономічні публікації, 2017)
The questions of the ionosphere refraction account at radiosources observation on the radiotelescope URAN-4 at 20-25 MHz are considered. The experimental data are received which will be coordinated to results of ionosphere refraction modeling.